Galvanomagnetic phenomena in HgMnTe and HgCdMnTe single crystals - Ostapov, S.E.; Rarenko, I.M.; Tymochko, M.D. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
This paper presents theoretical and experimental investigations of narrow-gap semiconductors HgMnTe and HgCdMnTe. It has been shown that the comparison of temperature dependencies of the conductivity and Hall coefficient in the mixed conductivity region makes it possible to determine the content of cadmium and manganese, as well as the concentration of doping acceptor impurity.